Real-Time Data Integration and Weather Reporting Automation with Cloud Computing-based Interactive Spatial Dashboard for Extreme Weather Risk Analytics in Indonesia - Arifani, Kahpi Baiquni; Pintarko, Dody; Sari, Anggraini Puspita; Agussalim, Agussalim (Information Technology and Science (ITScience), 2025)
Global climate change has increased the risk of extreme weather events in Indonesia, necessitating an accurate and real-time weather information system. This study develops a cloud computing-based system capable of integrating national weather data in real-time, automating the generation of actual and forecast weather reports, and presenting this information through an interactive spatial dashboard. The system is built on a client-server architecture deployed on Google Cloud Platform, utilizing the OpenWeatherMap API, a Flask backend, and a JavaScript-based frontend (Leaflet.js and Chart.js). Evaluation results indicate that the system can provide integrated national weather data with latency under one second, generate automated multi-province weather reports, and deliver interactive heatmap visualizations of extreme weather risks. This system is effective in improving the speed, accuracy, and efficiency of weather information distribution to support decision-making in the maritime, transportation, and disaster management sectors.